ANALISA STATISTIK DESKRIPTIF PENYERAPAN DANA BAGI HASIL CUKAI HASIL TEMBAKAU (DBH CHT) OLEH PEMERINTAH DAERAH PADA TAHUN ANGGARAN 2021 – 2023 - Amodha, Javas Hasthoka; Purnomo (JURNAL PERSPEKTIF BEA DAN CUKAI, 2025)
The Tobacco Excise Sharing Fund (DBH CHT) constitutes a portion of the financial allocations transferred from the central government to local governments, which are determined based on a specific percentage of state revenue derived from excise taxes generated within their respective regions. The establishment of DBH CHT is mandated by the prevailing Excise Law. The deployment of DBH CHT has been meticulously regulated to facilitate various programs across several domains, including the health sector, community welfare sector, law enforcement sector, and additional activities. Enhancing the efficacy of DBH CHT utilization is imperative to meticulously monitor the budget absorption associated with DBH CHT. This study endeavors to ascertain the effectiveness of DBH CHT absorption by Local Government entities. The research methodology employed is descriptive statistics coupled with a quantitative approach. The data utilized comprises secondary data reflecting the realization of DBH CHT utilization by Local Governments throughout Indonesia during the period from 2021 to 2023. The findings indicated that budget absorption falls within the moderately effective category, specifically within the range of 70% to 90%. Regarding the deployment of DBH CHT in the law enforcement sector, it has not been utilized to its full potential, as evidenced by a budget absorption rate of merely 50% in 2021. Conversely, for activities in other sectors, such as the health sector, the community welfare sector, and various other activities, the absorption rates are relatively effective, falling within the range of 70% to 90%.